Intranasal supernumerary tooth: two case reports and review of the literature - Mario Rašić; Matija Mamić; Josip Biočić; Ivica Lukšić (University of Zagreb. School of Dental Medicine, 2023)
The presence of supernumerary tooth (SNT) in the nasal cavity is a rare condition with limited literature data. We report two cases with a history of nasal obstruction and difficulty breathing. In both cases, clinical and radiological examination confirmed intranasal SNT. Extractions were executed in general anesthesia using Rochester-Pean instruments transnasally. In addition, a literature review of intranasal SNT was performed. The database search retrieved a total number of 50 cases in time period from 1970. to 2020. Mean age of patients was 22.5 years. Most common symptoms were unilateral obstruction of breathing and headache. Surgical extraction of intranasal SNT is recommended to eliminate the symptoms.